2004
DOI: 10.1073/pnas.0308475101
|View full text |Cite
|
Sign up to set email alerts
|

SIX1 mutations cause branchio-oto-renal syndrome by disruption of EYA1–SIX1–DNA complexes

Abstract: Urinary tract malformations constitute the most frequent cause of chronic renal failure in the first two decades of life. Branchio-otic (BO) syndrome is an autosomal dominant developmental disorder characterized by hearing loss. In branchio-oto-renal (BOR) syndrome, malformations of the kidney or urinary tract are associated. Haploinsufficiency for the human gene EYA1, a homologue of the Drosophila gene eyes absent (eya), causes BOR and BO syndromes. We recently mapped a locus for BOR͞BO syndrome (BOS3) to hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
381
3
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 384 publications
(393 citation statements)
references
References 27 publications
7
381
3
2
Order By: Relevance
“…In vertebrates, it has been demonstrated that EYA1/2 and SIX1 interact physically and are expressed in sensorial placodes as well as in the developing kidney. Consistently, mutations in either Eya1 or Six1 underlie the branchio-oto-renal (BOR) syndrome, which is characterized by anomalies of face, ear, and kidneys (Abdelhak et al, 1997;Ruf et al, 2004;Kozlowski et al, 2005). Furthermore, EYA2 cooperates with SIX1 and DACH2 to regulate muscle development (Heanue et al, 1999), and reported activities of EYA3 in cell culture depend on the presence of SIX1 (Li et al, 2003).…”
Section: Potential Protein Interaction Partners Of Eya3mentioning
confidence: 91%
“…In vertebrates, it has been demonstrated that EYA1/2 and SIX1 interact physically and are expressed in sensorial placodes as well as in the developing kidney. Consistently, mutations in either Eya1 or Six1 underlie the branchio-oto-renal (BOR) syndrome, which is characterized by anomalies of face, ear, and kidneys (Abdelhak et al, 1997;Ruf et al, 2004;Kozlowski et al, 2005). Furthermore, EYA2 cooperates with SIX1 and DACH2 to regulate muscle development (Heanue et al, 1999), and reported activities of EYA3 in cell culture depend on the presence of SIX1 (Li et al, 2003).…”
Section: Potential Protein Interaction Partners Of Eya3mentioning
confidence: 91%
“…In humans, mutations in SIX1 have been found to be linked to the Branchio Oto Renal Syndrome (BOR, OMIM 113650), a genetic disorder that includes malformations of the ear and cysts in the neck, hearing loss, and malformations of the kidney. According to the autosomal dominant mode of BOR inheritance, the corresponding mutations in human SIX1 appears to confer dominant-negative properties to the transcription factor (Kochhar et al, 2008, Ruf et al, 2004. One of the antimorphic human mutations disrupts the conserved valine at position 17, right next to the cysteine mutated in the zebrafish fr16 allele (Fig.…”
mentioning
confidence: 99%
“…Patients with BOR/BO syndrome may have conductive, sensorineural, or mixed type hearing loss which may be stable or progressive with severity ranging from mild to profound [Fraser et al, 1980]. To date, mutations in three genes, EYA1 [Abdelhak et al, 1997], SIX1 [Ruf et al, 2004;Ito et al, 2006], and SIX5 [Hoskins et al, 2007], have been found in patients with BOR/BO syndrome.…”
Section: Introductionmentioning
confidence: 99%